2006
DOI: 10.3139/146.101227
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and surface properties of liquid Ga–Tl and Zn–Cd alloys

Abstract: A simple thermodynamic model, based on the formation of self-associates, has been used to correlate the bulk and surface properties of mixing of liquid Ga–Tl and Zn–Cd alloys at temperatures of 973K and 900K, respectively. The model enables us to explain the positive deviation of the properties of mixing of the two liquid alloys from the ideal solution behavior. Our calculations indicate that the degree of phase separation in Zn–Cd, as measured using the Warren–Cowley short-range order parameter, is less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
4
3
0
Order By: Relevance
“…Although, in these figures, due to lack of experimental data, it is not possible to compare computed and experimental results, however, in Fig. 5, the results obtained at 800 and 900 K are in agreement with that reported in [4,9] (where at 800 K, the tendency for phase separation is maximum around equiatomic composition, and at 900 K, minimum diffusivity is 0.4 at C Zn ¼ 0:56). Thus, these agreements serve as evidence of the reliability of the following observations in Fig.…”
Section: Surface Properties Modelsupporting
confidence: 92%
See 4 more Smart Citations
“…Although, in these figures, due to lack of experimental data, it is not possible to compare computed and experimental results, however, in Fig. 5, the results obtained at 800 and 900 K are in agreement with that reported in [4,9] (where at 800 K, the tendency for phase separation is maximum around equiatomic composition, and at 900 K, minimum diffusivity is 0.4 at C Zn ¼ 0:56). Thus, these agreements serve as evidence of the reliability of the following observations in Fig.…”
Section: Surface Properties Modelsupporting
confidence: 92%
“…In the figure, we observed that at all temperatures, S cc ð0Þ [ S cc ð0; idÞ. This is an indication that Zn-Cd liquid alloys are homocoordinated (in agreement with the reports in [4,7,9]), and that the homocoordination which is weak is indicated by the relatively low peak at various temperatures, when compared with strongly homocoordinated alloys like Ga-Tl liquid alloys [9]. The figure also show that, when the temperature is increased, the position of maximum S cc ð0Þ shifts towards equiatomic composition, the values of S cc ð0Þ at all composition of Zn approach that of ideal solution (in agreement with the report in [7], from the study of experimental thermodynamic activity of Zn-Cd alloys at 800 and 900 K) and becomes nearly symmetrical about equiatomic composition (in agreement with the reports in [6,7]).…”
Section: Surface Properties Modelsupporting
confidence: 89%
See 3 more Smart Citations